2014
DOI: 10.4172/1948-5948.s8-008
|View full text |Cite
|
Sign up to set email alerts
|

Production of Microbial Lipids from Rice Straw Hydrolysates by Lipomyces starkeyi for Biodiesel Synthesis

Abstract: To minimize the cost of biodiesel production, massively available biomass, rice straw was selected as starting material for fermentation by oleaginous yeast, Lipomyces starkeyi. Acid hydrolysis was carried out to obtain Rice Straw Hydrolysates (RSH). Maximum amount of glucose was liberated with 3.5% H 2 SO 4. Highest levels of biomass (~12 g/L) and lipid content (~36%) of L. starkeyi were obtained through fermentation of RSH produced with 3.5% H 2 SO 4. The optimum pH for biomass yield and lipid accumulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…On the basis of these results, peptone was designated as the best nitrogen source for both lipid accumulation and biomass production. Similarly, it has been reported that peptone as an organic nitrogen source enhanced biomass and oil production by Tolyposporium ehrenbergii, Sphacelotheca reiliana, Lipomyces starkeyi, and Tricosporon fermentans (Farag et al, 1983;Zhu et al, 2008;Azad et al, 2014). Inorganic nitrogen sources such as ammonium nitrate and potassium nitrate were found to be favorable for lipid accumulation during the cultivation of Cunninghamella japonica and Aspergillus versicolor, respectively (Lunin et al, 2013;Karatay and Doenmez, 2014).…”
Section: Influence Of Different Nitrogen Sources On Fungal Biomass Anmentioning
confidence: 86%
“…On the basis of these results, peptone was designated as the best nitrogen source for both lipid accumulation and biomass production. Similarly, it has been reported that peptone as an organic nitrogen source enhanced biomass and oil production by Tolyposporium ehrenbergii, Sphacelotheca reiliana, Lipomyces starkeyi, and Tricosporon fermentans (Farag et al, 1983;Zhu et al, 2008;Azad et al, 2014). Inorganic nitrogen sources such as ammonium nitrate and potassium nitrate were found to be favorable for lipid accumulation during the cultivation of Cunninghamella japonica and Aspergillus versicolor, respectively (Lunin et al, 2013;Karatay and Doenmez, 2014).…”
Section: Influence Of Different Nitrogen Sources On Fungal Biomass Anmentioning
confidence: 86%
“…Azad et al [78] optimized pH values of a fermentation broth containing H2SO4-hydrolysated RS as a carbon source for Lipomyces starkeyi, and found that the yeast accumulated microbial lipids up to 36.14% of cell dry weight (CDW). Diwan et al [150] developed an effective H2SO4 based mild saccharification of RS and successfully employed the crude, non-detoxified hydrolysate for growth of the yeast Mortierella alpina MTCC-6344 that accumulated lipids up to 40% of CDW.…”
Section: Biodieselmentioning
confidence: 99%
“…The growth and biomass production of fungi vary when cultured under different cultivation conditions [23,24]. These conditions are generally affected by several parameters, including pH [18,25]. The biomass production by R. oligosporus in sago effluent under different initial pH is presented in Fig.…”
Section: Propagation and Accumulation Stage Of Submerged Fermentation Of R Oligosporus In Sago Effluentmentioning
confidence: 99%